Valuasi Ekonomi Monumen Perjuangan Rakyat Jawa Barat: Analisis Konseptual Willingness to Pay dalam Upaya Pelestarian Sejarah - Muhammad Raihan Firdaus; Mentari Ramadani; Witri Saren Simanjorang; Danu Anugrah Saputra; Khabib Fathurahman; Rexcy Zihad Tri Hidayat; Fauzie Hakim Mulyady; Muhammad Azka Nursyifa (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The People’s Struggle Monuments of West Java represent public cultural assets that embody historical memory, collective identity, and social values embedded in public space. Preservation efforts have often relied on government funding, creating structural vulnerability when fiscal priorities shift. This study aims to conceptually analyze the economic valuation of struggle monuments through the willingness to pay approach as a strategy for sustainable heritage preservation. Using a qualitative conceptual-analytical method, this research synthesizes policy frameworks, cultural heritage theories, and empirical findings from previous valuation studies. The analysis demonstrates that willingness to pay reflects not only economic capacity but also public perception, historical awareness, emotional attachment, and trust in monument management. Integrating willingness to pay into preservation policy provides empirical justification for participatory funding mechanisms, improves policy legitimacy, and strengthens community involvement. This approach positions heritage preservation as a shared social responsibility rather than a solely governmental obligation. The study contributes to the literature on cultural heritage economics by extending willingness to pay analysis to struggle monuments and offers a conceptual foundation for policy development that aligns historical preservation with sustainable public participation.